A Qualitative Study of Breast Reconstruction Decision-Making among Asian Immigrant Women Living in the United States. Issue 2 (February 2017) - Fu, Rose; Chang, Michelle Milee; Chen, Margaret; Rohde, Christine Hsu
Abstract : Background: Despite research supporting improved psychosocial well-being, quality of life, and survival for patients undergoing postmastectomy breast reconstruction, Asian patients remain one-fifth as likely as Caucasians to choose reconstruction. This study investigates cultural factors, values, and perceptions held by Asian women that might impact breast reconstruction rates. Methods: The authors conducted semistructured interviews of immigrant East Asian women treated for breast cancer in the New York metropolitan area, investigating social structure, culture, attitudes toward surgery, and body image. Three investigators independently coded transcribed interviews, and then collectively evaluated them through axial coding of recurring themes. Results: Thirty-five immigrant East Asian women who underwent surgical treatment for breast cancer were interviewed. Emerging themes include functionality, age, perceptions of plastic surgery, inconvenience, community/family, fear of implants, language, and information. Patients spoke about breasts as a function of their roles as a wife or mother, eliminating the need for breasts when these roles were fulfilled. Many addressed the fear of multiple operations. Quality and quantity of information, and communication with practitioners, impacted perceptions about treatment. Reconstructive surgery was often viewed as cosmetic. Community and family played a significant role in decision-making. Conclusions: Asian women are statistically less likely than Caucasians to pursue breast reconstruction. This is the first study to investigate culture-specific perceptions of breast reconstruction. Results from this study can be used to improve cultural competency in addressing patient concerns. Improving access to information regarding treatment options and surgical outcomes may improve informed decision-making among immigrant Asian women.